2020
DOI: 10.1186/s12935-020-01251-6
|View full text |Cite
|
Sign up to set email alerts
|

N-alkylisatin-based microtubule destabilizers bind to the colchicine site on tubulin and retain efficacy in drug resistant acute lymphoblastic leukemia cell lines with less in vitro neurotoxicity

Abstract: Background: Drug resistance and chemotherapy-induced peripheral neuropathy continue to be significant problems in the successful treatment of acute lymphoblastic leukemia (ALL). 5,7-Dibromo-N-alkylisatins, a class of potent microtubule destabilizers, are a promising alternative to traditionally used antimitotics with previous demonstrated efficacy against solid tumours in vivo and ability to overcome P-glycoprotein (P-gp) mediated drug resistance in lymphoma and sarcoma cell lines in vitro. In this study, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…A number of studies have differentiated the SH-SY5Y cell line with RA for a short duration of 2–4 days, at which point the cells are then treated with a chemical factor, to evaluate the inhibitory or stimulatory effect on neurite outgrowth over a specified period 13 , 29 , 30 . However, such short differentiation protocols would be insufficient to produce a population of terminally differentiated cells 31 .…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have differentiated the SH-SY5Y cell line with RA for a short duration of 2–4 days, at which point the cells are then treated with a chemical factor, to evaluate the inhibitory or stimulatory effect on neurite outgrowth over a specified period 13 , 29 , 30 . However, such short differentiation protocols would be insufficient to produce a population of terminally differentiated cells 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Following application of paclitaxel, a common chemotherapeutic used for several types of cancers, rat DRG neurons manifest altered excitability due to higher expression of voltage-gated potassium, hyperpolarizationactivated cyclic nucleotide-gated (HCN), and voltage-gated sodium channels together with a decrease in the expression of inwardly-rectifying potassium channels (Zhang and Dougherty, 2014). Ion channels have a critical role in the development and progression of peripheral neuropathies hence, strides have been made towards the development of cancer therapies aimed at curtailing excitability remodeling and neurotoxicity (Keenan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…VCR, known initially as Leurocristine, is the first-line chemotherapeutic medication often administered in the combination chemotherapeutic treatment of pediatric hematologic malignancies and solid tumors [ 53 ]. VCR acts as mitotic inhibitors by binding to the β-tubulin subunit of αβ-tubulin heterodimers, thus functionally destabilizing microtubule fibers, which ultimately leads to the termination of cancer cell division [ 54 ]. Previous studies have shown a cumulative effect for its neurotoxicity and overdosage may cause very serious or fatal outcomes [ 55 , 56 ].…”
Section: Severe Neuropathy and Myopathy Side Effects In Chemotherapymentioning
confidence: 99%